Low voltage varistor ceramics based on SnO2 - Dhage, S. R.; Ravi, V.; Yang, O. B. (Bulletin of Materials Science, 2007)
The nonlinear current (I)-voltage (V) characteristics of tin dioxide doped with either Nb2O5 and CoO or Sb2O3 and CoO show promising values of nonlinear coefficient (alpha) values (similar to 11) with low breakdown voltages (E-B, similar to 40 V mm(-1)). The pentavalent antimony or niobium acts as donor and increases the electronic conductivity. The crucial parameter for obtaining low breakdown voltage is the grain size, which depends upon sintering duration and temperature of these oxide ceramics.
Keywords: Chemical synthesis; electronic materials; Microstructure; tin oxide; X-ray diffraction